RAISE: A Self-Hosted Platform for Mining and Managing Data from GitHub and Jira - Neves, Breno; Coutinho, Daniel; Sardenberg, Eduardo; Alesi, Arthur; Machado, Marcelo; Arriel, Johny; Cavalvante, Ana Luísa; Carvalho, Robbie; Pereira, Juliana Alves (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2025: Anais do XIX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2025)
The growing number of software repositories has opened new opportunities for researchers to investigate how software is developed, howteams collaborate, and howquality evolves over time. However, mining useful information out of these repositories often requires custom, ad hoc scripts tailored to specific studies, which are rarely built to be reusable or shareable. This hinders reproducibility, results in redundant data extraction efforts, and wastes computational resources, particularly in academic environments where multiple researchers or teams may need similar datasets. To address these limitations, we developed RAISE, a self-hosted platform for mining and managing data from GitHub and Jira. RAISE offers both an REST API and a web-based interface, allowing streamlined data retrieval, exploration, and export. It is built with widely adopted technologies such as Django, Docker, Celery and React. It is easy to deploy, supports background task execution, and ensures consistent behavior across environments. The platform provides fine-grained filtering, integrates data from both local and remote repositories, and stores results in a structured database for reuse. To evaluate the RAISE’s practical value and usability, we performed a user-centered evaluation with six participants, who engaged in a range of realistic repository mining tasks of varying complexity.